Improvement of spring canola Brassica napus by use of winter canola - Habibur Rahman,; Berisso Kebede, (Journal of Oilseed Brassica, 2026)
Further improving of seed yield, other agronomic and seed quality traits in spring canola Brassica napusrequires broadening of genetic diversity in this crop. The European winter oilseed B. napus is known to begenetically diverse from spring oilseed B. napus. We hypothesized that elite spring canola B. napus lineswith greater seed yield and genetic diversity can be achieved through the use of European winter B. napus.For this, a winter x spring B. napus breeding program was undertaken at the University of Alberta, andpedigree and doubled haploid breeding techniques were applied. Spring canola lines with significantly increasedseed yield were obtained in one cycle of breeding. Estimates of genetic diversity based on SSRmarkers revealed that some of the spring canola lines derived from winter x spring crosses possess greaterdiversity compared to the spring parents. The major constraint of this winter x spring breeding is that latenessof flowering and maturity are generally introduced into the spring type lines which would require repeatedcycle of breeding for improvement.